Multiple Sclerosis: Associations Between Physical Disability and Depression Are Not Mediated by Self-Reported Physical Activity. Issue 5 (October 2017) - Merkt, Helene; Sadeghi Bahmani, Dena; Calabrese, Pasquale; Naegelin, Yvonne; Gerber, Markus; Pühse, Uwe; Holsboer-Trachsler, Edith; Brand, Serge
This study investigated the interrelatedness of physical disability, physical activity, and depression among patients with multiple sclerosis (MS). We hypothesized that self-reported physical activity would mediate the effect of disability on depressive symptoms. Twenty-seven patients with MS (mean age: 49 years; 44.5% females) completed self-rating scales covering sociodemographic variables, intake of antidepressants, physical activity, and symptoms of depression; disability was measured by the Expanded Disability Status Scale. We found a higher level of disability to be significantly associated with more symptoms of depression. While higher reported physical activity was descriptively associated with lower depression scores and unrelated to Expanded Disability Status Scale, physical activity levels did not mediate the effect of disability on depressive symptoms.